Efforts to Increase Free Regional Original Income on the Ponorogo Regency Regional Tax Road-Map for 2022-2026 - Yulia Krismya Putri; Rochmat Aldy Purnomo; Yeni Cahyono; Slamet Santoso; Sayid Abas (MediaTrend, 2022)
Local tax revenue is the largest source of local revenue. Conditions in Ponorogo Regency in the local tax revenue sector have decreased in 2020 due to the Covid-19 pandemic. The government must prepare a strategy and design to recover lost tax revenues in 2020. Projections are made to find out the amount of local tax revenue, especially in Ponorogo Regency in the coming 2022-2026. This study aims to calculate and project the value of regional tax revenue for Ponorogo Regency in 2022-2026 and design activities so that these projections can be fulfilled. Secondary data obtained from the Office of Revenue, Financial Management and Regional Assets of Ponorogo Regency. The largest revenue from the Regional Tax for Ponorogo Regency in 2013-2021 is land and building taxes with a total of 250,443,706,350 and the lowest is the groundwater tax post which only reaches 1,862,439,630. However, after making projections for 2022-2026 the largest tax post occurs in total hotels with a value of 6,072,824,558 and the lowest tax post occurs with a parking tax of 722,938,090. The value of the highest tax item has changed in the hotel tax post as well as the hidden tax item in the parking tax which has changed in its entirety from before the projection was carried out. So it is necessary to renew new activity programs in order to increase tax items that are still low and maintain tax items that are already large.